Prevalence of burnout syndrome and perception by playing position in professional football players - Rodrigo Weyll Ferreira; Victor Silveira Coswig; Pedro Antonio Marques da Silva Monteiro; Jhonatan Welington Pereira Gaia; Eduardo Macedo Penna; Daniel Alvarez Pires (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: The present study aimed to investigate the indicators of burnout, to determine whether playing position affects the perception of syndrome dimensions, and to identify burnout prevalence in professional football players. Methods: The participants were 100 professional football players (mean age 24.3 ± 4.6 years and meantime as a professional athlete of 9.2 ± 4.5 years) who were divided into three groups: 27 forwards, 34 midfielders, and 39 defenders. The Athlete Burnout Questionnaire (ABQ) and a sociodemographic questionnaire were applied. Results: The results show that a) the majority of athletes had low burnout indicators, b) there was no difference in the perception of burnout dimensions by playing position, and c) the prevalence of athletes with burnout, whether mild, moderate, or severe, was 13%. Conclusion: The variable of playing position was not a determinant of perception of burnout dimensions among the forwards, midfielders, and defenders. Nonetheless, the prevalence of burnout deserves attention, as the negative effects of this syndrome may exert impacts on health, well-being, and sports performance, making athletes more likely to abandon their sport.